The meaning of happiness for nuns - Rihani, Desi; Nugroho, Hieronymus Rony Suryo (Universitas Mercu Buana Yogyakarta, 2024)
Happiness is everyone’s goal of all ages, occupations, and social statuses. Because it is a subjective concept, happiness depends on different standards and factors from each individual. Externally, happiness includes property, social life, age, health, education, and religion. While internally, happiness includes positive emotions, and a person's perspective to see their past, present, and future. People strive to gain power, wealth, and life partners to achieve happiness. Nevertheless, there is a group of individuals, namely the Catholic nuns, who actually fight for their happiness without being tied to wealth, life partners, and social status. The main purpose of this research is to find out the description of happiness in the life of nuns, and how the nuns can achieve this happiness. The participants in this study were three nuns, each representing a monastic age: junior, medior, and senior. Data was collected using a semi-structured interview method, with a natural setting. Observations were conducted in a participatory manner by researchers. The research questions posed were: first, what was the source of happiness for nuns; second, how did the nuns achieve happiness; third, what was the meaning of happiness for nuns. The results of this study showed that the source of the happiness of nuns was the experience of being loved by God and inner depths. Nuns achieve happiness by reflecting on daily experiences, spiritual practice, and developing gratitude. The meaning of happiness for nuns is a close relationship with God and service to others. This paper also puts forward constructive suggestions for nun’s formation or education. So, the novice formandi can balance the spiritual and human aspects.